(untitled) (Texas Journal of Medical Science, 2022)
Post covid syndrome can develop in all patients who have had COVID-19, regardless of the severity of the disease. The clinical picture of post covid syndrome is very diverse, but the most common are asthenic disorders, anxiety-depressive disorders (TDD) and cognitive impairment (CN).